Controlled/living radical polymerization of methyl methacrylate in the presence of 2-bromoethanol as a transfer agent and comparison with cumyl dithiobenzoate as a RAFT agent - Akmal Hadi, Ma' Radzi; Hairul Nazirah, Abdul Halim; Zulfakar, Mokhtar; Mohamed Zulkali, Mohamed Daud (Asian Network for Scientific Information, 2010)
Link to publisher's homepage http://www.scialert.net/